All because of competition: A bane or blessing for smaller licence buying companies (LBCs) of the Ghanaian cocoa industry - Goodlet Owusu Ansah; Isaac Antwi; Lawrencia Pokuah Siaw (Cogent Business & Management, 2017)
The dynamic global market in the world of business forces firms to initiate quick and favourable actions in order to stay active in this ever-changing world of business. The study investigated the post liberalization and privatization effect of competition on smaller Licensed Buying Companies (LBCs) in the Ghanaian Cocoa industry using the Kuapa Kokoo Limited' (KKL) situation. The study also sought to unravel the nature of competition and challenges stemming from the competition among LBCs. The study utilized the Herfindahl–Hirschman Indexes and the K-concentration ratio to examine the nature of competition in the industry. Responses were gathered from one hundred and twenty-three (N = 123) employees of KKL. The study revealed that, competition exists in the cocoa industry but is greatly controlled by LBCs with larger market shares and that out of this emanate threats for smaller LBCs in the cocoa industry. The study indicated that major challenges stemming from the competition included unfair influence by LBCs, bamboozlement of smaller LBCs by well-established bigger LBCs, breach of agreements between LBCs and farmers etc. It is therefore recommended that the present cocoa purchasing regulations be adequately enforced to better control the effects of unhealthy competitions in the internal market of the cocoa industry.
Keywords: 650